Inhibition of TnA translocation by TnA. - Robinson, M K (1977)
Plasmids already containing TnA showed decreased susceptibility to the translocation of a further TnA unit when compared with related plasmids that did not contain TnA. The translocation immunity imposed by TnA is exerted only on the plasmid of which it is part. It is suggested that this desensitization by a translocation unit is a general phenomenon that reduces the mutational effects of translocation.